2018
DOI: 10.5194/bg-15-6167-2018
|View full text |Cite
|
Sign up to set email alerts
|

The ability of macroalgae to mitigate the negative effects of ocean acidification on four species of North Atlantic bivalve

Abstract: Abstract. Coastal ecosystems can experience acidification via upwelling, eutrophication, riverine discharge, and climate change. While the resulting increases in pCO2 can have deleterious effects on calcifying animals, this change in carbonate chemistry may benefit some marine autotrophs. Here, we report on experiments performed with North Atlantic populations of hard clams (Mercenaria mercenaria), eastern oysters (Crassostrea virginica), bay scallops (Argopecten irradians), and blue mussels (Mytilus edulis) g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 92 publications
0
17
0
Order By: Relevance
“…Multiple aspects of the carbonate system have been shown to have impacts on marine biota. Reductions in CO 3 2availability and O a below critical thresholds have been shown to represent a stressor to a variety of shelled marine invertebrates (e.g., Clements et al, 2017Clements et al, , 2018Rheuban et al, 2018;Young and Gobler, 2018;Pousse et al, 2020) including crabs, lobsters, oysters, scallops, and mussels in the GOM (Tables S1 and S2). The pH can impact physiological processes that rely on the transfer of [Hþ], including olfactory senses in fish (e.g., Dixson et al, 2015) and crab megalopae (Miller et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple aspects of the carbonate system have been shown to have impacts on marine biota. Reductions in CO 3 2availability and O a below critical thresholds have been shown to represent a stressor to a variety of shelled marine invertebrates (e.g., Clements et al, 2017Clements et al, , 2018Rheuban et al, 2018;Young and Gobler, 2018;Pousse et al, 2020) including crabs, lobsters, oysters, scallops, and mussels in the GOM (Tables S1 and S2). The pH can impact physiological processes that rely on the transfer of [Hþ], including olfactory senses in fish (e.g., Dixson et al, 2015) and crab megalopae (Miller et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Less frequent field experiments also support adverse OA effects in bivalves as evidenced by reductions in settlement rates when low pH conditions prevail in sediments for Mya arenaria and Nucula spp (Table S1). An increased repertoire of studies, including more species, different life stages, multiple concurrent stressors, field and lab experiments, modeling projections, transgenerational observations (Griffith and Gobler, 2017), and potential for mitigation in multispecies studies (Young and Gobler, 2018), have considerably improved the understanding of potential responses to OA for individual bivalve species in the GOM.…”
Section: Sensitivity Of Gom Fauna To Oamentioning
confidence: 99%
“…The presence of spatial and temporal variability in CO 2 chemistry across marine ecosystems has raised the idea that ocean acidification refugia (OAR), or locations where ocean acidification impacts could be less intense, exist naturally (Manzello, Enochs, Melo, Gledhill, & Johns, 2012). Proposed OAR include seagrass meadows and dense algal beds (Hendriks et al, 2014;Krause-Jensen et al, 2015;Manzello et al, 2012;Unsworth, Collier, Henderson, & Mckenzie, 2012;Wahl et al, 2018;Young & Gobler, 2018), algal boundary layers (Cornwall et al, 2014; F I G U R E 1 Processes modifying ocean acidification exposures over a range of temporal frequencies and spatial scales. (a) Seasonal pH regimes driven by warming in a temperate ecosystem and primary production in a polar ecosystem (Kapsenberg, Alliouane, et al, 2017;Kapsenberg et al, 2015).…”
mentioning
confidence: 99%
“…In an ecosystem setting, kelp beds may provide a refuge to grazers by simultaneously buffering carbonate chemistry and providing ample quantities of food. Previous studies have demonstrated the ability of macroalgae to buffer carbonate chemistry and promote the growth and survival of calcifying organisms (Wahl et al 2018, Young & Gobler 2018. However, such a buffering effect can be species-and/or site-specific (Rivest et al 2017).…”
Section: Discussionmentioning
confidence: 99%